Bitch planet (2014), volume 2 ebook President bitch. - DeConnick, Kelly Sue (Bitch Planet (2014), 2018)
Eleanor's gambit: The "PRESIDENT BITCH" arc concludes. BITCH PLANET will return in August.. Author: Kelly Sue Deconnick. Illustrator: Valentine De Landro, Taki Soma . 2017 Milkfed Criminal Masterminds, Inc..